2014
DOI: 10.1186/s13045-014-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of telomeres and telomerase in hematologic malignancies and hematopoietic stem cell transplantation

Abstract: Telomeres are specific nucleoprotein structures at the ends of eukaryotic chromosomes. Telomeres and telomere-associated proteins maintain genome stability by protecting the ends of chromosomes from fusion and degradation. In normal somatic cells, the length of the telomeres gradually becomes shortened with cell division. In tumor cells, the shortening of telomeres length is accelerated under the increased proliferation pressure. However, it will be maintained at an extremely short length as the result of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 94 publications
1
37
0
5
Order By: Relevance
“…This is the first study on CLL focusing on TL dynamics on a large cohort of patients. This study shows that: (i) progressive telomere erosion occurs during the natural history of CLL and is higher than the YL described in healthy subjects (20-59 bp) (Wang et al, 2014); (ii) telomere loss is more pronounced when baseline TL is higher; (iii) accelerated telomere loss is associated with an inferior TFS, identifying a subgroup of patients that, despite a TL still far from critical levels, are likely to progress.…”
mentioning
confidence: 69%
“…This is the first study on CLL focusing on TL dynamics on a large cohort of patients. This study shows that: (i) progressive telomere erosion occurs during the natural history of CLL and is higher than the YL described in healthy subjects (20-59 bp) (Wang et al, 2014); (ii) telomere loss is more pronounced when baseline TL is higher; (iii) accelerated telomere loss is associated with an inferior TFS, identifying a subgroup of patients that, despite a TL still far from critical levels, are likely to progress.…”
mentioning
confidence: 69%
“…It is shown that cells from old donors or patients with telomerase deficiencies had limited replication ability, rendering the cell number necessary for HSCT insufficient [19] . Moreover, in patients who had received HSCT, the telomere length of engrafted stem cells is closely related to the outcomes of transplantation, thus highlighting the significance of telomere status during donor selection [20] . Therefore, some authors speculate about advantages of cord blood HSCs use, which are related to longer telomeres and higher replication ability than HSCs in bone marrow [19] .…”
Section: Importance Of Telomere Maintenance For Stem Cell Propertiesmentioning
confidence: 99%
“…Como consequência, este conjunto de fatores pode levar à seleção de células anormais e progressão maligna (surgimento de neoplasias) ou à aplasia celular (telomeropatias) (BARTHEL et al, 2017). (HARTMANN et al, 2005;WANG et al, 2014;CHU et al, 2017). (KLAPPER et al, 2003).…”
Section: Discussionunclassified
“…AALBERS et al, 2013;EL BELBESY et al, 2015).Os telômeros são significativamente mais curtos nas células leucêmicas com citogenética anormal quando comparados àquelas sem anormalidade, sendo que os pacientes com cariótipos com múltiplas aberrações têm os telômeros mais curtos(CAPRARO et al, 2011). Além da citogenética, comprimento telomérico encurtado e aumento da atividade da telomerase também se correlacionam com a progressão da doença e recaída(WANG et al, 2014). LMA e LLA, a atividade da telomerase correlaciona-se com a expressão de TERT, e é maior no momento do diagnóstico ou progressão do que no momento da remissão(CAPRARO et al, 2011).…”
unclassified
See 1 more Smart Citation